عزل وتشخيص الانواع البكتيرية من اقدام نوعين من طيور البط المدجنه في محافظة البصره - حسن قاسم (University of Thi-Qar Journal of Science, 2010)
The bacteria was isolated from the foots of 25 birds from aquatic birds mallard (Anas platyrhynchos)(5 male and 10 female) and pintail (Anas acuta)(3male and7 female) collected from different locations from Basrah province and the bacteria was idenitified to 05 species of bacteria 1- Serratia plymuthica 2– Enterobacter sakazakii 3-Clostridium histolyticum 4- Staphylococcus saprophyticus5- Pseudomonas aeruginosa 6- E.coli 7- Salmonella orizonae 8- Kluyvera ascorbata 9- Citrobacter braakii 10- Clostridium carnis 11- Serratia odorifera 12- Bacillus firmus 13- Citrobacter freundii 14- Citrobacter diversus 15- Staphylococcus sciuri.The data analysis T.test and the correlation coefficient between weight increase and bacterial percentage was significant at p<0.05 and difference 0f bacteria species according to the birds sex.